Korelasi Emotional Quotient (EQ) terhadap Motivasi Belajar Mahasiswa Program Studi Pendidikan Agama Islam - Salsabila, Aida Zahra; Baharudin, Baharudin; Yusnita, Erni; Octafiona, Era; Romlah, Listiyani Siti (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
This research on the correlation of Emotional Quotient (EQ) to Student Learning Motivation aims to measure the relationship or relationship between emotional intelligence and learning motivation. This research uses a quantitative approach with a type of correlation research. While data collection uses questionnaire distribution (non-test) with simple random sampling technique. While data analysis uses the product moment correlation model to determine the relationship between the two independent variables to the dependent variable. The results of this study indicate that a correlation value of 0.476 was found which indicates that the two variables or emotional quotient variables with learning motivation have a moderate correlation category. Found a significant value of .000, where the significant value < .01 which means there is a significant relationship between emotional quotient and learning motivation of Islamic Education Study Programme Students, UIN Raden Intan Lampung.